Comparison of 2D and 3D Numerical Procedures in Analysing Piled Raft Foundations Under Different Loading Conditions - Gamage, D.H.P.; Abayakoon, S.B.S. (Journal of Engineering Issues and Solutions, 2025)
Piled rafts are considered as effective ways to minimize settlements in raft foundations while improving the bearing capacity at the same time. Due to the complex nature of the interactions between the three elements; soil, piles and raft, analysis of a piled raft has become a daunting task. Among the available methods for analysis of piled-rafts, the use of two-dimensional software is an interest, when it comes to computer hardware capacity, time consumption and associated cost, in comparison to 3D analysis. The 3D problem is simplified to a 2D problem by introducing plane strain properties with corresponding smeared parameters. This paper presents a systematic study that compares 2D analyses to corresponding 3D analyses for a variety of material, geometric and loading conditions.PLAXIS 2D is one such software that can be used to analyse piled rafts. For piled rafts with equally spaced and identical piles subjected to a uniform vertical load, PLAXIS 2D analysis overestimates settlement by approximately 45%. Despite the inherent limitations of PLAXIS 2D, reasonably closer values for horizontal displacement can be obtained for piled rafts subjected to lateral loads, with values varying between –30% and +18% compared to field measurements and 3D analysis results. However, for piled rafts under non-uniform combined loading, the horizontal deformation results obtained from PLAXIS 2D can be overestimated by up to 140% compared to 3D analysis.